Proglacial methane emissions driven by meltwater and groundwater flushing in a high-Arctic glacial catchment - G. E. Kleber; G. E. Kleber; G. E. Kleber; L. Magerl; A. V. Turchyn; S. Schloemer; M. Trimmer; Y. Zhu; Y. Zhu; A. Hodson; A. Hodson (Biogeosciences)
Glacial groundwater is a conduit for geologic methane release in areas of glacier retreat on Svalbard, representing a large, climate-sensitive source of the greenhouse gas. Methane emissions from glacial melt rivers are known to occur in other regions of the Arctic, but such emissions have not yet been considered on Svalbard. Over the summer of 2021, we monitored methane concentrations in the proglacial groundwater springs and river network of an ∼ 20 km2 valley glacier in central Svalbard to estimate melt season emissions from a single catchment. We measured methane concentrations in the glacial river of up to 3170 nM (nearly 800 times higher than the atmospheric equilibrium concentration) and found the methane to be of thermogenic origin through isotopic analysis. We estimated a total of 1.0 t of methane emissions during the 2021 melt season from the catchment, of which nearly two-thirds are being flushed from the glacier bed by the melt river. These findings provide further evidence that terrestrial glacier forefields on Svalbard are hotspots for methane emissions, with a climate feedback loop driven by glacier melt. As the first investigation into methane emissions from glacial melt rivers on Svalbard, our study suggests that summer meltwater flushing of methane from beneath the ∼ 1400 land-terminating glaciers across Svalbard may represent an important seasonal source of emissions. Glacial melt rivers, including those from small valley glaciers, may be a growing emission point for subglacial methane across other rapidly warming regions of the Arctic.